1997
DOI: 10.1111/j.1151-2916.1997.tb03232.x
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic Assessment of the Silver–Oxygen System

Abstract: An assessment of the silver–oxygen system has been made, and a consistent set of thermodynamic parameters has been optimized. The calculated thermodynamic properties and phase relations are in good agreement with the experimental data. Ag2O is the only phase that is commonly found within the system. In air, it decomposes to silver and oxygen gas at 420 K. There is a eutectic between silver and Ag2O at a temperature of 804 K, an oxygen partial pressure (PO2) of 526 bar (5.26 × 107 Pa), and an oxygen mole fracti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(48 citation statements)
references
References 23 publications
2
46
0
Order By: Relevance
“…It suggests that no reaction took place between BaTiO 3 and silver during calcinations and sintering. Thermodynamic studies have suggested that silver is more stable than Ag 2 O at temperatures of >189.8 • C in air [15]. Therefore, any Ag 2 O that is present decomposes to metallic silver during the calcination heating-up stage.…”
Section: Resultsmentioning
confidence: 99%
“…It suggests that no reaction took place between BaTiO 3 and silver during calcinations and sintering. Thermodynamic studies have suggested that silver is more stable than Ag 2 O at temperatures of >189.8 • C in air [15]. Therefore, any Ag 2 O that is present decomposes to metallic silver during the calcination heating-up stage.…”
Section: Resultsmentioning
confidence: 99%
“…Despite the fact that the sintering process was conducted in air, no silver oxide is found in BiT/Ag composites. Since silver is more stable than silver oxide above 189.8 • C in air [18] and the formation of Ag 2 O is a very slow process at low temperature [19], the amount of Ag 2 O formed during the cooling stage may be too little to be detected via the XRD technique. The X-ray diffraction results indicate that metallic Ag phase is compatible with BiT matrix.…”
Section: Resultsmentioning
confidence: 99%
“…As shown earlier, linear trends in ASR with time are observed, and the degradation rate of silver-ESB composites at 650 °C was reduced from 4.10 × 10 -4 Ωcm 2 /h to 1.91 × 10 -5 Ωcm 2 /h-a 95% drop with the reduced ESB particle size. mobility in silver 40,41 and, as shown earlier, the application of a bias across the cell leads to an electro-migration effect where the silver phase is dragged along in the direction of oxygen flux.…”
Section: Improving Stability and Area Specific Resistance Through Micmentioning
confidence: 52%